An interactive videogame for arm and hand exercise in people with Parkinson's disease: A randomized controlled trial. (August 2017) - Allen, Natalie E.; Song, Jooeun; Paul, Serene S.; Smith, Stuart; O'Duffy, Jonathan; Schmidt, Matthew; Love, Rachelle; Sherrington, Catherine; Canning, Colleen G.
Abstract: Introduction: People with Parkinson's disease (PD) have difficulty performing upper extremity (UE) activities. The aim of this study was to investigate if exergames targeting the UE improve arm and hand activities and impairments and to establish the acceptability and feasibility of these games in people with PD. Methods: Two tablet-based exergames were developed which were controlled with finger movements or unimanual whole arm movements. Participants with PD were randomized to an exergame (n = 19) or control (n = 19) group. The exergame group performed UE exergames at home, 3 times per week for 12 weeks. The primary outcome measure was the nine hole peg test. Secondary outcomes included measures of UE activities and impairments, including the tapping test [speed (taps/60s), and error (weighted error score/speed)]. Results: There were no between group differences in the nine hole peg test, or in any secondary outcome measures except for the tapping test. Horizontal tapping test results showed that exergame participants improved their speed (mean difference = 10.9 taps/60s, p  < 0.001) but increased error (mean difference = 0.03, p  = 0.03) compared to the control group. Participants enjoyed the games and improved in their ability to play the games. There were no adverse events. Conclusion: The UE exergames were acceptable and safe, but did not translate to improvement in functional activities. It is likely that the requirement of the games resulted in increased movement speed at the detriment of accuracy. The design of exergames should consider task specificity. Highlights: We investigated the efficacy of exergames for the upper extremity (UE) in PD. The exergame group did not improve UE activity performance compared to control. The exergame group increased UE movement speed but reduced movement accuracy. Results may be explained by specificity of task practice. We recommend considering specificity of task practice in the design of exergames.